Kontribusi Stabilitas Emosi Terhadap Kemampuan Pembuatan Keputusan Karier Siswa SMP - Ahmad Fajri (Universitas Mathla'ul Anwar Banten, 2017)
Contributions Emotion Stability to Career Decision Making Ability of SMP Students. This research is motivated by the career decision-making abilities of students of class IX are still easily influenced by the environment, it is because students feel anxious not appropriate selection of subsequent studies. Identified emotion stability can provide a positive influence on career decision-making abilities, like not anxious, to understand the feelings of others, and is able to accept the other person's perspective. In general the studies carried out to determine the contribution of emotion stability to the career decision-making abilities of students class IX SMPN 26 Bandung Academic Year 2016/2017. The research approach using a quantitative approach to the study correlational. The samples used were all students of class IX SMPN 26 Bandung academic year of 2016/2017 as many as 286 people. The results showed that (1) the emotion stability of students that are in the category of less stable with a percentage of 66.4%, (2) the ability of making career decisions of students in the category capable with a percentage of 53.5%, (3) there is a positive contribution and significant emotion stability of 16.7% against the career decision-making abilities of students, meaning that the diversity of career decision-making ability scores of students of class IX SMPN 26 Bandung determined by emotion stability student of 16.7%. The results of this analysis can be considered state aid students in the focus of guidance and counseling services.